MODERN FAIRY TALES: FEMINIST IN COLLECTION OF SHORT STORIES MEREKA BILANG SAYA MONYET WORK DJENAR MAHESA AYU - Ahmad Bahtiar; Gunta Wirawan; Suryo Ediyono (Proceeding of International Conference on Art, Language, and Culture, 2017)
This paper attempts to illustrate the patriarchal cultural issues contained in the collection of short stories Mereka Bilang Saya Monyet work Mahesa Djenar Ayu. In the collection, Djenar trying to use culture to deconstruct the form of fairy tales that the women at a disadvantage. As with any fairy tale, Djenar using animal characters such as leeches, monkeys, and dogs in these works. Generally eleven story short story a lot of surrealism. Based on these work Djenar tried to do for the resistance against the hegemonic gender is not only for women but for human dignity in general.